2010
DOI: 10.1123/jab.26.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness and Endurance of a Locking Compression Plate Fixed on Fractured Femur

Abstract: The effects of locking screw position (long column fixation—long distance between the nearest screws to the fracture—and short column fixation—short distance between the nearest screws to the fracture) and fracture gap size (1-mm and 8-mm transverse fracture gap) on stiffness and fatigue of fractured femur fixed with a locking compression plate (LCP) were biomechanically evaluated. The stiffness of 1-mm fracture gap models and that of intact femoral model were in the range of 270–284 N/mm, while those of 8-mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 14 publications
2
21
1
1
Order By: Relevance
“…The plates used in this study also were stainless steel, however, testing in that study was performed using peak loads slightly greater than the elastic limit, whereas we used loads that were 65% of the elastic limit. All the plates in that study [19] and ours broke through the screw holes closest to the defect, consistent with two additional studies that showed the greatest amount of stress in the plate is at the screw holes nearest the defect [2,24].…”
Section: Discussionsupporting
confidence: 65%
“…The plates used in this study also were stainless steel, however, testing in that study was performed using peak loads slightly greater than the elastic limit, whereas we used loads that were 65% of the elastic limit. All the plates in that study [19] and ours broke through the screw holes closest to the defect, consistent with two additional studies that showed the greatest amount of stress in the plate is at the screw holes nearest the defect [2,24].…”
Section: Discussionsupporting
confidence: 65%
“…Maxwell et al reported similar results when screw placement was evaluated in 3.5 mm dynamic compression plates and limited contact dynamic compression plates applied in a fracture gap model [11]. Recent studies comparing the cyclic fatigue properties of plates applied with a short and long working length found that the constructs with a longer working length withstood more cycles before failure, although the differences between stabilization techniques were not significant [5,9]. …”
Section: Introductionmentioning
confidence: 95%
“…Plate working length has been shown to influence construct stiffness, plate strain and cyclic fatigue properties of the plate [5,8-11]. The lack of load sharing between the stabilized bone and the implants increases the risk of cyclic fatigue and early failure of the implant [9,12]. A mechanical study evaluating the mechanical endurance of human femora stabilized with 14-hole broad 4.5 mm LCPs found that constructs with load sharing resisted 20 times more cycles than the constructs with an 8 mm segmental diaphyseal gap [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, quanto maior a capacidade elástica de deformação da placa em ponte, menor seu risco de quebra ou fadiga. 17 Com modelos artificiais de fêmur, Hoffmeier et al 18 e Kanchanomai et al 19 observaram redução na tensão superficial de placas bloqueadas em aço inoxidá-vel e em titânio quanto maior a área de trabalho do implante. Isso mostra que comportamento de fadiga dependente, dentre outros fatores relacionados à técnica de osteossíntese, da área de trabalho.…”
Section: Discussionunclassified